Histologic evaluation of AlphaCor keratoprosthesis explanted following various complications - Jiraskova, Nada; Werner, Liliana; Mamalis, Nick; Rozsival, Pavel (Biomedical papers, 2014)
Aims: To report the histological findings in two AlphaCor artificial corneas explanted following complications,to compare the mechanism of biointegration and/or failure of the device and the correlation with clinical histories.Methods: The first patient was diagnosed with optic deposits and corneal melting during the late postoperative period and required the removal of the device. The second patient experienced injury with penetration of the device 5 months after implantation. The explanted devices embedded within the corneal tissues were processed for pathological analysis at the John A. Moran Eye Center, University of Utah, Salt Lake City, USA. Histologic findings were compared with earlier histological results from animal studies and human case series and correlated with clinical histories.Results: Both devices demonstrated normal skirt porosity. Light microscopic examination of the specimens disclosed adequate biointegration - colonization of the peripheral skirt with cellular elements present within the pores of the skirt. In the first patient (specimen 1) epithelial ingrowth was observed between the peripheral skirt and the posterior surface of the specimen, with partial extrusion of the device in that area. In the second case (specimen 2) the central, optic component of the device was missing.Conclusion: Histologic findings of the AlphaCor skirt were consistent with earlier animal studies and human cases series reports. These findings confirm the occurrence of biointegration. Epithelial ingrowth and scattered chronic mononuclear inflammatory cells were observed in the area of partial extrusion in the patient with a history of melting prior to explantation.
Keywords: AlphaCor; keratoprosthesis; biointegration; histology